Economic Viability of Palm Kernel Oil Processing in Ahoada East LGA, Rivers State, Nigeria - Bendre, Neeta (Journal of Global Economy, Business and Finance, 2026)
This research looked at the economics of palm kernel oil processing in Rivers State's Ahoada East Local Government Area. The work precisely characterized the socioeconomic traits of processors of palm kernel oil, assessed the processing costs, identified the issues facing processors of palm oil and indicated the causes of the palm kernel oil enterprise's dropping production. Seven villages were purposefully chosen from each of the three clans for a total of twenty-one villages; twenty communities were proportionally chosen from the three clans. Additionally, three palm kernel oil producers were chosen at random from each village, yielding a total of 63 respondents for the study. The data were examined using descriptive statistics and gross margin analysis. According to the data, there were primarily female respondents (70.0%) and male respondents (30.0%), whose active ages ranged from 41 to 50 years. Compared to singles, divorcees, and widows, married people (60.0%) were more active. The average respondent's household size is between 1 and 5, their educational background is 40.0%, and their years of experience are between 1 and 5. The gross margin was N96,700 and the profit were N77,700 per month. Palm kernel oil sales brought in a total of N328,000, with a total expense of N250,300. The main difficulties experienced by the research area's respondents are the high transportation costs for obtaining the raw materials, the expensive palm kernel fruit the poor road that led to the expensive palm kernel seed the scarcity of palm kernel fruit, the high cost of hiring equipment for the process of making palm oil, and the lack of access to credit facilities. In conclusion, the study's findings demonstrate Ahoada East Local Government Area, Rivers State, palm kernel oil processors were lucrative. According to the report, the government could expand road building into rural areas by repairing feeder roads, which will improve traffic issues.